Cost Reduction for Knee-Spanning External Fixation in the Staged Treatment of Tibial Plateau Fractures: A Practical Intervention. Issue 5 (May 2022) - Only, Arthur J.; Hayek, Kevin; McCreary, Dylan L.; Huyke, Fernando A.; Siljander, Breana; Kibble, Kendra; Cunningham, Brian P.
Abstract : Objective: To determine whether an educational intervention affects surgeon implant decision making measured by total implant costs for temporizing a knee-spanning external fixation construct. Design: A total of 24 cases were prospectively collected after an educational intervention and matched to 24 cases before intervention using Schatzker classification and by surgeon. Setting: A single Level 1 trauma center. Patients/Participants: Forty-eight patients with Schatzker II-VI tibial plateau fractures. Intervention: Education session to create transparency with component pricing and to provide 3 clinical cases of Orthopaedic Trauma Association/AO 41-C3 (Schatzker VI) with accompanying images and fixator construct costs. Total implant costs displayed in the session ranged from 2354 to 11, 696. Outcome Measurement: External fixator construct cost. Results: The mean cost of constructs in the postintervention group was 4550.20 [95% confidence interval (CI) 3945.60–5154.00], which was significantly different compared with the preintervention group cost of 6046.75 (95% CI = 5309.54–6783.97, P = 0.003). After 1 year, the total implant costs of external fixation constructs were reduced by an average of almost 1500 per patient. Conclusion: An educational intervention created a reduction in the average total implant construction costs for temporary knee-spanning external fixation in the treatment of tibial plateau fractures. Surgical implant selection and cost variance remain an ideal area to improve value for patients and hospitals. Empowering surgeons with knowledge regarding implant prices is a critical part of working toward the cost reductions of external fixation constructs.